Gossamer [compact disc, unabridged] - Lowry, Lois (Random House/Listening Library, 2006)
While learning to bestow dreams, a young dream giver tries to save an eight-year-old boy from the effects of both his abusive past and the nightmares inflicted on him by the frightening Sinisteeds.